Analysis of urban youth perceptions of Paraguayan rural space - Salinas Vera, Diana Emilce (2022)
Rural space in Paraguay is characterized by great complexity and diverse situations, which, as well as the perceptions of such spaces, are in constant transformation. The objective of this paper is to analyze the visions and interpretations that urban youth have about Paraguayan rural space. The methodology adopted was the bibliographic and documentary review of primary and secondary information, as well as a survey with closed and open questions to 32 senior students from Colegio Area 1 of Ciudad del Este. Results indicate that students’ perceptions of rural Paraguay refer to a “quiet” place, with little access to services, smaller population, large green spaces, and no pollution, despite the fact that the country has high levels of deforestation and fumigation. Subjects, in general, associate countryside “nature” and “green spaces” much more with productive spaces than with preservation areas. However, most of the answers see rural Paraguay as a space for family farming and a pleasant place, permeated with a certain nostalgia.